Toll-like receptor expression and function in type I bipolar disorder - Wieck, Andrea; Grassi-Oliveira, Rodrigo; do Prado, Carine Hartmann; Viola, Thiago Wendt; Petersen, Laura Esteves; Porto, Bárbara; Teixeira, Antônio Lúcio; Bauer, Moisés Evandro (Brain, behavior, and immunity, 2016)
•BD subjects have differential distribution and functioning of TLR1/2 monocytes.•Cells of BD subjects secrete more IL-1β and IL12-p70 in response to TLR1/2 agonists.•BD patients had increased percentages of TLR2+ and TLR5+ T cells (incl. Treg).•Impaired TLR signaling may contribute to the inflammation profile observed in BD.•TLR alterations were negatively correlated to years of disease in BD subjects. Bipolar disorder (BD) has been associated with immune imbalance and low-grade inflammation. The underlying mechanisms remain largely obscure but may involve changes in cell signaling. Toll-like receptors (TLRs) are widely expressed by immune cells. Specific binding of TLRs to pathogen- or danger-associated signals leads to inflammatory responses. Here, we analyzed the frequencies of TLR-1, TLR-2, TLR-4, TLR-5 and TLR-6 in monocytes, regulatory T cells (Tregs) and activated T cells from type I BD euthymic patients and healthy controls (HCs). Monocytes were stimulated in vitro with specific TLR agonists (flagellin, LPS, LTA, BLP and PGN) and immunophenotyped. Cytokines (IL-8, IL-1beta, IL-6, IL-10, TNF-alpha and IL-12p70) were assessed with cytometric bead arrays. At baseline, increased percentages of TLR-1+ and TLR-2+ monocytes and reduced expression of TLR-5 were observed in BD. Following stimulation, the percentage of TLR-1+, TLR-2+, and TLR-6+ monocytes was higher in BD subjects than in HCs. Increased levels of IL-8, IL-12p70 and TNF were observed following stimulation with TLR-1, TLR-2 and TLR-6 agonists, suggesting increased signaling via these receptors in BD. In contrast to HCs, BD patients exhibited no changes in TLR-5 expression following stimulation. The percentage of TLR-2+ Treg cells as well as activated T cells expressing both TLR-2 and TLR-5 increased in BD patients. Given the importance of TLRs in triggering immune responses, our data indicate a role for these receptors in the low-grade inflammatory profile documented in BD.